Pendidikan Kebencanaan Berbasis Komunitas Lokal untuk Guru SMAN Rikit Gaib - Sahudra, Tengku Muhammad; Harahap, Hanif; Kenedi, Ary Kiswanto; Ramadhani, Dini; Mardin, Asna; Zuliana, Zuliana (Universitas Pahlawan Tuanku Tambusai, 2025)
This community engagement program aimed to enhance teachers’ capacity in disaster mitigation and to develop a disaster curriculum based on local social-community wisdom at SMAN 1 Rikit Gaib, Gayo Lues Regency, an area prone to landslides and flash floods. The methods used included public education, training, technology transfer, and advocacy, employing a participatory approach. The results showed a significant improvement in teachers’ understanding, with an average post-test score increase of 73.9%. Teachers also successfully developed a thematic curriculum that integrates local wisdom into classroom learning. Additional outputs included evacuation route maps, teaching modules, and a School Emergency Response Plan (RTDS). These outcomes demonstrate that contextual training based on local knowledge is effective in fostering school disaster preparedness. This program serves as a strategic model for replicating disaster education in other high-risk regions.